GAG mimetic functionalised solid and mesoporous silica nanoparticles as viral entry inhibitors of herpes simplex type 1 and type 2 viruses. Issue 36 (7th September 2016) - Lee, Edward C.; Davis-Poynter, Nicholas; Nguyen, Chau T. H.; Peters, Amelia A.; Monteith, Gregory R.; Strounina, Ekaterina; Popat, Amirali; Ross, Benjamin P.
Abstract : Mesoporous and solid silica nanoparticles functionalised with a novel glycosaminoglycan (GAG) mimetic inhibit the cellular attachment and penetration of herpes simplex virus (HSV). Abstract : A glycosaminoglycan mimetic was attached to the surface of solid and mesoporous silica nanoparticles to create novel antiviral agents against herpes simplex type 1 and type 2 viruses. The nanoparticles act as viral entry inhibitors that appear to block viral attachment and penetration into susceptible cells.